PENGEMBANGAN OBJEK WISATA BERBASIS POTENSI ALAM - Nelly Pardede; Erika Revida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research is motivated by the fact that there are still problems with the Bah Biak Waterfall tourist attraction, such as accessibility, facilities that are still damaged and inadequate, the absence of a tourism organization that manages the Bah Biak Waterfall and poor management. optimally, so there needs to be development that can be implemented well by the relevant department, namely the Simalungun Regency Culture, Tourism and Creative Economy Service.The research method used in this research is descriptive qualitative. The informants in this research consisted of the Head of the Simalungun Regency Tourism Culture and Creative Economy Service, the Sidamanik District Head, the Bah Biak Waterfall manager, the community around the Bah Bak Waterfall tourist attraction and tourists. This research uses development indicators proposed by M Liga Suryadana, namely Attraction Objects, Facilities, Accessibility, Institutions, Management Institutions and Hospitality.The results of this research show that the development carried out by the Department of Culture, Tourism and Creative Economy has not been optimal, in terms of attractiveness, the development carried out is only limited to building a mini park and swimming pool which is right under the Bah. Biak Waterfall. The facilities and developments carried out are not optimal, such as the condition of toilets and parking lots. Accessibility, development has not been carried out due to the PTPN IV Bah Biak Waterfall Tourism Business Use Rights. Management Institutions still only create Tourism Awareness Group and Travel Agent programs. Hospitality, development carried out through tourism awareness programs. The obstacles faced are the lack of community participation in the tourism sector, limited support and maintenance of supporting facilities, lack of cooperation with investors and the absence of a promotion system. The supporting factor for its development is that Bah Biak Waterfall has good capital and natural potential.